An Investigation Into Code-Switching In Conversations Of Foreigners In Hoi An - Võ Thị Lệ (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
Ancient Hoi An city has become the most famous and charming destination, attracting many tourists from all over the world. Hoi An wins the hearts of tourists with its laid-back life style and the sincerity, plainness and enthusiasm of its residents [56]. As a result, many people from different countries make a decision to work and live in this old city. They do many types of jobs to financially support their lives such as; tour guide, hotel assistant, teacher, diving instructor, business-person, office manager, or receptionist and so on. It is not unusual for Hoi An natives to see non Vietnamese people speaking Vietnamese rather fluently beside their mother tongues. The usage of half- foreign and half-native language in speech or in discussion is referred to as ‘code-switching in conversations’. The purpose of this study is to examine the use of elements of Vietnamese language within English discourse by native English speakers living and working in Hoi An. In addition, this paper attempts to focus on features motivating code switching in conversations. The data for analysis includes recordings of normal social interactions, and conversational interviews, a questionnaire and written observation sheets. This study also examines the purposes of code switching and how it is used to achieve plasticity as well as the speakers’ communicative intents in Vietnamese-English bilingual conversations of native English speakers. Finally, it is hoped this study will lead readers to a better understanding of code-switching in Vietnamese-English bilingual conversations.